The Impact of the COVID Pandemic on Adrenal Surgery at an Academic Endocrine Surgery Unit - Chiapponi, Costanza; Faust, Michael; Schmidt, Matthias; Schier, Robert; Thomas, Michael; Stippel, Dirk L.; Bruns, Christiane Josephine; Alakus, Hakan (Hormone and Metabolic Research, 2023)
COVID-19 has severely affected the delivery of surgical care worldwide. The aim of the present study was to evaluate its impact on adrenal surgery at our academic endocrine center. All primary adrenal surgeries performed at the University Hospital of Cologne, Germany between 01.01.2019 and 31.07.2022 were included. This time frame was divided into pre-Covid (before 02/20), acute Covid (until 05/21), and post acute period (after 05/2021). Demographics, clinic-pathologic characteristics and treatment of these patients were analyzed. One hundred adrenalectomies were included: 22 before, 30 during, and 48 after the acute phase. The percentage of Conn adenomas and pheochromocytomas decreased during the acute phase (from 45.4 to 26.6% and from 18 to 10%, respectively) in favor of Cushing adenomas and suspicious tumors (from 4.5 to 20% and from 31.8 to 36.6%). About 90.9% of tumors resected for suspicion of malignancy were confirmed malignant by final histopathology, as opposed to 71.4% and 52.6% before and after the acute phase. The operative technique was similar during the three phases (63% retroperitoneoscopic, 34% laparoscopic and 2% open resections), with a significantly shorter operative time for retroperitoneoscopy (p=0.04). ICU monitoring demand increased during the acute phase (from 13.6% to 43.3%), according to the increase in Cushing adenomas and malignant tumors. During the acute phase of COVID-19 pandemic adrenal surgery for Cushing and malignant tumors increased, while a delay in pheochromocytoma surgery to the post acute phase was observed. The suspicion of malignancy formulated by the endocrine tumor board was accurate in 90.9% of cases.
Keywords: adrenal surgery; COVID-19; pandemic; endocrine tumor board